The Use of Conceptual Metaphor in the Interpretive Analysis of Political Discourse - Maciej Bachryj (Politeja)
This article considers the possibility of integrating conceptual metaphor theory (CMT), developed within the realm of cognitive linguistics, with an interpretive approach to political science. The author demonstrates that the theoretical tenets of cognitive linguistics correspond to the ontological and epistemological foundations of the interpretive perspective. Moreover, he points to the need to consider language and meaning-making linguistic processes as an important area for interpretive analysis in political science and shows how CMT can contribute to this task. Finally, the paper signals possible research objectives of such analyses and the potential areas where they could be applied.